Coastal current in the northern region of the east coast of Peninsular Malaysia - Saadon, Mohd Nasir; Camerlengo, Alejandro Livio; Wan Kadir, Wan Hazli (Penerbit Universiti Kebangsaan Malaysia, 1997)
This study provides new information on the coastal current along the northern region of the east coast of Peninsular Malaysia. A self-recording S4 current meter, 3 m deep, from July to September 1996, about one nautical mile from the coastline of Kuala Terengganu, was used to determine the speed and direction of the coastal current. The results confirm the presence of coastal current along the northern region of the east coast of Peninsular Malaysia, during the southwest (SW) monsoon season. The coastal current has a maximum speed of over 30 cm/s. Its direction off low is affected by tide. It flows northward (southward) during ebb (flood) tide. However, its net direction of flow is southeastward.